2014
DOI: 10.1155/2014/191847
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography for Macular Edema

Abstract: Optical coherence tomography (OCT) is a rapid noncontact method that allows in vivo imaging of the retina and it has become an important component in clinical practice. OCT is a useful ancillary tool for assessing retinal diseases because of its ability to provide cross-sectional retinal images and quantitatively analyze retinal morphology. The introduction of spectral-domain OCT provided major improvements in image acquisition speed and image resolution. Future studies will address how these major technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Spectral domain-OCT (SD-OCT) has proved to be very useful in the accurate detection of normal and pathologic structures, which is important for the diagnosis of ocular diseases. [ 8 ] Several techniques have been developed for automated robust segmentation of retinal layers, choroid, and choroid vessels. [ 9 10 11 12 13 ] However, studies with simultaneous assessment of retina, choroid, and choroid vessels from OCT images are still lacking.…”
mentioning
confidence: 99%
“…Spectral domain-OCT (SD-OCT) has proved to be very useful in the accurate detection of normal and pathologic structures, which is important for the diagnosis of ocular diseases. [ 8 ] Several techniques have been developed for automated robust segmentation of retinal layers, choroid, and choroid vessels. [ 9 10 11 12 13 ] However, studies with simultaneous assessment of retina, choroid, and choroid vessels from OCT images are still lacking.…”
mentioning
confidence: 99%
“…Optical coherence tomography as a noninvasive technique which has been frequently preferred recent years in terms of evaluating macular thickness and RNFL in patients with glaucoma has been used by physicians (24,25). Obese children were measured in our study and a significant differences were found to be in retinal parameters.…”
Section: Discussionmentioning
confidence: 81%
“…No significant difference was seen with the 1st week, 1st month, 3rd month, 6th month and 12th month comparisons of total macular volume, central macular thickness, parafoveal area thickness, perifoveal area thickness and RNFL thickness (p>0.05). photography and fluorescein angiography are commonly used for the diagnosis of macular edema, the evaluation of their results may vary from person to person, and small changes in the early stages of macular edema may also be overlooked (12).…”
Section: Resultsmentioning
confidence: 99%